A case of diffuse midline glioma, H3 K27M mutant mimicking a hemispheric malignant glioma in an elderly patient. Issue 1 (24th November 2019) - Fujioka, Yutaka; Hata, Nobuhiro; Hatae, Ryusuke; Suzuki, Satoshi O.; Sangatsuda, Yuhei; Nakahara, Yukiko; Mizoguchi, Masahiro; Iihara, Koji
Abstract : Diffuse midline glioma, H3 K27M mutant arises from midline structures of the central nervous system and predominately affects pediatric patients. However, this disease entity was only recently established, and the clinical phenotypic spectrum remains largely unclear. We herein report a rare case of diffuse midline glioma, H3 K27M mutant with an unusual distribution in an elderly woman who presented with a diffuse glioma that invaded both sides of the thalami, and left hippocampus and frontoparietal lobes, thus mimicking a hemispheric malignant glioma. A biopsy of the lobular lesion led to a molecular diagnostic confirmation of diffuse midline glioma, H3 K27M mutant. The patient received concurrent bevacizumab and temozolomide therapy with radiation therapy and survived for 30 months. This case highlights the possibility that a glioma with cerebral hemispheric spread in an elderly patient may harbor the H3 K27M mutation.